Molecular simulations and visualization: introduction and overview - Hirst, J.D.; Glowacki, D.R.; Baaden, M. (Royal Society of Chemistry, 2014)
Here we provide an introduction and overview of current progress in the field of molecular simulation and visualization, touching on the following topics: (1) virtual and augmented reality for immersive molecular simulations; (2) advanced visualization and visual analytic techniques; (3) new developments in high performance computing; and (4) applications and model building.